CHOCOLATE CYST – A COMPLEX OVARIAN ENDOMETRIOMA - BHABNA SAHA (International Journal of Pharma and Bio Sciences, 2014)
Chocolate cyst, a complex ovarian cyst, resembles that of a chocolate coloured sac, grows on the outer surface of the ovary containing old menstrual fluid and affects women of reproductive ages. The cause of its formation is unknown but many hypothesises are proposed. Ultrasonography and laparoscopy are the two conventional methods of diagnosis but present day researchers concentrate on use of biomarkers. Based on diagnosis of endometrial patches, it can be staged I-IV. These are treatable with hormones, painkillers, laparoscopy, laparotomy and oopherectomy, but are incurable. As it affects women of reproductive age group, it causes hindrance in fertility and assisted reproductive methodologies are recommended. The most challenging property of chocolate cyst is its recurrence nature which makes it incurable to date and finding its solution is an area of interest of present day researchers and can fetch a hope for the affected individuals.